POETIC IDEAL IN THE WORK OF OSMAN AZIM - Turgunova Mahliyo Nuriddin qizi (Journals Park Publishing, 2023)
In the article, the poems of Osman Azim are drawn into the framework of analysis, the brilliance of the writer's work, the special creativity of his greatness is revealed traditional, ideological and artistic interpretation. In the poem of Osman Azim, the effect of shakily research related not only to content, but also to band forms is covered
Keywords: quartet, Ghazal, eights, mukhammas, poetic genre , aruz vase, hijran dashti, raddi matla.